(NtEKTONI^ESKIE KRITERII SEJSMI^NOSTI `VNOJ qKUTII (B/s - (NiMAEW(B, (NwALERIJ sULEJMANOWI^s; (NgUSEW(B, (Ng(B.(Ns(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 118-125s
(Nan sssr(B. (NsIB(B. (NOTD(B-(NNIE(B. (NqKUTSKIJ FIL(B. (NiN(B-(NT GEOLOGIIs
Keywords: (NsEJSMI^NOSTXs -- (NqKUTIQs